Pengaruh Cash Holding, Bonus Plan dan Ukuran Perusahaan terhadap Income Smoothing dengan Reputasi Auditor sebagai Variabel Moderating pada Indonesia Most Trusted Companies Tahun 2016-2022 Corporate Governance Perception Index - Pakpahan, Putri Elisabeth; Fachrudin, Fachrudin; Satriawan, Bambang (Universitas Batanghari Jambi, 2025)
The aim of this research is to determine the effect of cash holding, bonus plan and company size on income smoothing with auditor reputation as a moderating variable on the Indonesia Most Trusted Companies 2016-2022 Corporate Governance Perception Index (CGPI), with a purposive sampling technique research sample of 10 companies. . The data analysis used is the Last Squares Dummy Variable (LSDV) and Moderate Regression Analysis (MRA) techniques. The research results show that partially the cash holding variable has a positive and insignificant effect on income smoothing. Bonus plan, company size and auditor reputation have a positive and significant effect on income smoothing at Indonesia Most Trusted Companies CGPI. In moderation, the auditor reputation variable cannot moderate the relationship between cash holding and income smoothing, but the auditor reputation variable can weaken and strengthen the relationship between bonus plans and income smoothing and company size and company size with income smoothing in the Indonesia Most Trusted Companies CGPI.